Konsep Kota Pintar Yang Diterpakan Pada Pelayanan Umum di Bidang Transportasi - Hendratna, Gempa; Damuri, Amat; Anagora, Roni; Syah Putra, Arman (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
In this research, the field of transportation is a field that is raised in its research problem,with the development of smart cities, transportation is also developing, systemdevelopment continues to improve the deficiencies of the existing system, the problemraised in this study is the online bus booking system that can help a lot. The public inordering tickets, in this study using the literature review method by reading a lot of thelatest journals in order to find the latest problems, in this study the author applies theconcept of the city of Pinta to existing transportation problems, with the development ofthis system it will produce an intestinal system. a new one to make it easier for the publicto order bus tickets.